A Systematic Review of Telehealth Applications in Endocrinology - SeyedAhmad SeyedAlinaghi; Soudabeh Yarmohammadi; Pegah Mirzapour; Soheil Dehghani; Sepide Ahmadi; Faeze Abbaspour; Ava Pashaei; Ayoob Molla; Alireza Pashaei; Samin Ahmadi; Esmaeil Mehraeen (Telemedicine Reports)
Introduction: The prevalence of telehealth has witnessed a significant increase in various medical domains, especially in endocrinology. Telehealth brings about considerable advantages for both patients and health care professionals. However, despite these positive aspects, the growing prominence of telehealth is accompanied by certain challenges. This systematic review aims to assess the role of telehealth in endocrinology, including its applications, effectiveness, challenges, and implications for patient care. Methods: This study involved a thorough search using comprehensive techniques across databases such as PubMed/Medline, Embase, and Scopus. The studies were selected for a tailored adaptation of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) to enhance the clarity of our systematic review’s reporting. Results: This systematic review explores global telemedicine applications in endocrinology. Addressing various endocrine conditions, interventions utilize technology tools such as smartphones and applications, offering multifaceted utility from education and data gathering to screening and treatment. Notably, these interventions demonstrate adaptability during the COVID-19 pandemic. Positive outcomes include enhanced patient education, disease self-management, reduced complications, and improved glycemic control. However, drawbacks include the need for technical proficiency, perceived lower care quality, and potential privacy risks. These nuanced findings contribute to the discourse on telemedicine efficacy and limitations. Conclusion: In conclusion, telehealth holds significant potential in transforming endocrine care. While there are challenges to its implementation, the benefits it offers underscore its value as a health care delivery model.